A boy called Bat - Arnold, Elana K.; Santoso, Charles (New York, NY : Walden Pond Press, an imprint of HarperCollinsPublishers, 2017)
For Bixby Alexander Tam (nicknamed Bat), life tends to be full of surprises -- some of them good, some not so good. Today, though, is a good-surprise day. Bat's mom, a veterinarian, has brought home a baby skunk, which she needs to take care of until she can hand him over to a wild-animal shelter. But the minute Bat meets the kit, he knows they belong together. And he's got one month to show his mom that a baby skunk might just make a pretty terrific pet.
Ages 6-10.
Keywords: Autism -- Juvenile fiction; Skunks as pets -- Juvenile fiction; Wildlife rehabilitation -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Autism -- Fiction; JUVENILE FICTION / Family / Parents; JUVENILE FICTION / Social Themes / Friendship; JUVENILE FICTION / Social Themes / Special Needs; Autism; Human-animal relationships; Skunks as pets; Wildlife rehabilitation; Fiction; Juvenile works